PENERAPAN PEMBELAJARAN MATEMATIKA SMA PADA KURIKULUM MERDEKA BELAJAR DI BONTANG - Casmudi, Casmudi; Sugianto, Sugianto; Waskitoningtyas, Rahayu Sri (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Balikpapan, 2023)
This study aims to provide an overview of how to applying high school mathematics learning in the Merdeka Learning Curriculum in Bontang. The research method used in this study uses a qualitative descriptive method by collecting data through a questionnaire to obtain phenomena that occur regarding implementing the independent learning curriculum in high school mathematics learning. The number of subjects is 20 teachers from high schools in Bontang who have filled out a questionnaire. From the results of the observation about the application of vocational learning mathematics to the Free Learning Curriculum, there are still problems; for example, students' perceptions of mathematics are difficult, the learning media used by teachers is less interactive, teachers do not master technological developments, supporting facilities in learning mathematics are inadequate. It was concluded that implementing the Merdeka Learning curriculum in vocational mathematics learning requires more teacher innovation and creativity in designing models and media for learning mathematics that are more interactive so that students can easily understand and be given various questions to solve them